Microheater for microfluidic systems (2022)
Microfluidics devices have been a tool to develop low-cost alternatives for research in pharmaceutical, medical, and biomedical fields. This is because they allow miniaturizing the process and thus reduce the volumes of reagents needed. However, one of the most challenging variables to control within low-cost microfluidic devices is temperature due to the high costs of microheaters for microfluidic devices since they are manufactured in a clean room. This is why the need arises to simulate, design, and test a low-cost microheater that can be coupled to microfluidic devices. Electro-Thermal-Mechanical mathematical model was proposed in the COMSOL Multiphysics 6.0® software (COMSOL Inc., Stockholm, Sweden), which allowed an extensive study of different geometries for the microheater, allowing for varying both the number of turns of the microheater (m and n) and the distance between turns (w). After determining the optimal geometry with in silico studies, the micro heater was manufactured and characterized using an infrared thermometer and a thermal camera. The characterization determined an operational range for the microheater between 1v to 12v to reach temperatures between 25°C to 120°C. The simulations presented an error concerning the experimental results of 10.99955% with the Infrared Thermometer and 14.75182% with the Thermal Camera.